2018
DOI: 10.1111/iwj.12999
|View full text |Cite
|
Sign up to set email alerts
|

Effects and safety of atmospheric low‐temperature plasma on bacterial reduction in chronic wounds and wound size reduction: A systematic review and meta‐analysis

Abstract: The use of atmospheric low‐temperature plasma (AP) on chronic wounds and its effect on microbial bioburden in open wounds has not been explored with a systematic review and meta‐analysis. PRISMA guidelines were followed and PubMed, Embase, CENTRAL, and CINAHL databases searched for randomised controlled trials (RCTs), which compared AP with no AP for the management of open, chronic wounds. The primary outcomes of reduction of bioburden or wound size were included. Meta‐analyses were performed; odds ratio (OR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 55 publications
1
42
0
3
Order By: Relevance
“…For that reason, alternative wound healing therapies have been searched and extended. Very recently, special attention has been paid to the use of cold atmospheric pressure plasma (CAPP) in dermatology, thanks to the ability of these ionized-gas sources is to improve the wound healing process [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For that reason, alternative wound healing therapies have been searched and extended. Very recently, special attention has been paid to the use of cold atmospheric pressure plasma (CAPP) in dermatology, thanks to the ability of these ionized-gas sources is to improve the wound healing process [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, the interest of the controlled applications of CAPPs has rapidly increased. They include not only the utilization of CAPPs in dermatology [5][6][7][8][9][10][11][12][13][14][15][16][17][18], but also application of CAPP in the synthesis of nanomaterials [19][20][21], the germination of seeds [22], inhibiting the proliferation of cancers cell lines [23,24], and so on. This is possible because CAPP operation results in the generation of different reactive oxygen species (ROS, i.e., O 3 , H 2 O 2 , O•, O − 2 , OH•) and reactive nitrogen species (RNS, i.e., NO, NO 2 ), in addition to the emission of UV radiation and heat [7-9, 18, 25, 26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The promising role of CAP as a medical approach has also been described in dermatology, including the impact of CAP on atopic dermatitis, pruritus, or psoriasis [190]. Several studies demonstrated the positive effect of CAP on the eradication of bacterial infection in chronic wounds associated with the promotion of healing processes [191]. Cold plasma successfully eliminated bacterial colonisation in patients with chronic leg ulcers [19], chronic wounds [192], or chronic venous leg ulcers [193], and resulted in enhanced healing of chronic wounds.…”
Section: Plasma Promoted Wound Healing and Its Possibilities In The Smentioning
confidence: 99%
“…Since it is ideally suited to the treatment of surfaces, the fields of plasma medicine and plasma cosmetics often target the skin, healthy or diseased. CAP is already employed in the treat-DOI: 10.1159/000505195 ment of chronic wounds [2][3][4] and tested for the treatment of superficial tumors [5], warts [6], and many other indications as well as for cosmetic applications, such as skin rejuvenation [7,8].…”
Section: Introductionmentioning
confidence: 99%